A large free spectral range of 74.92 GHz in comb peaks generated by SU-8 polymer micro-ring resonators: simulation and experiment. (13th September 2018) - Ariannejad, M M; Amiri, Iraj S; Ahmad, H; Yupapin, P
Abstract: The feasibility of integrated SU-8 polymeric optical waveguides on a silicon platform was demonstrated experimentally and supported by simulation. Micro-ring resonator (MRR) configurations were designed and fabricated using SU-8 polymer. Simulation is carried out using the finite-difference time-domain method to improve the design. Both the simulation and experimental results confirm that SU-8 can be successfully used in the optical MRR. Passive MMI-coupled SU-8 single coupler and double coupler with a free spectral range of 74.92 GHz is achieved practically and corresponds with the simulation result. Moreover, other important parameters such as the full width at half maximum, Q factor and finesse are calculated from the simulation and practical results to support the feasibility of the SU-8 polymer MRR.